Exploring childhood mobility in Neolithic Southern France (Roquemissou) using incremental analyses of Sr isotope ratios in tooth enamel. (April 2022) - Coffin, Jeffrey; Dolphin, Alexis E.; Jackes, Mary; Yakymchuk, Chris; Perrin, Thomas
Highlights: Microspatial LA-MC-ICP-MS analyses of teeth mapped individuals' distinct patterns of mobility. 87 Sr/ 86 Sr ratios vary between individuals interred in the same burial shelter at Roquemissou. No shared directionality or seasonality of mobility was detected for these Neolithic people. Abstract: We use microspatial analysis of the changing ratios of 87 Sr/ 86 Sr across the growth bands of six third molars (M 3 s) to reconstruct the residence and mobility of children who lived in the region surrounding the village of Roquemissou, in Southern France, during the Late Neolithic. The results indicate strontium isotope ratios vary significantly between these individuals in both their average range and overall patterns, but the shift is very gradual in those who do change. This suggests that the people buried at this site were not seasonally mobile, but either moved over the course of years, or were entirely sedentary during the pre-adolescent years during which their M 3 s developed. Despite this lack of seasonal movement, the individuals buried at this site likely inhabited varied landscapes within a roughly 13 km radius of the site.